2003
DOI: 10.1177/0957154x030143003
|View full text |Cite
|
Sign up to set email alerts
|

Disappointment and Desolation: Women, Doctors and Interpretations of Puerperal Insanity in the Nineteenth Century

Abstract: Taking case notes as the key source, this paper focuses on the variety of interpretations put forward by doctors to explain the incidence of puerperal insanity in the nineteenth century. It is argued that these went far beyond biological explanations linking female vulnerability to the particular crisis of reproduction. Rather, nineteenth-century physicians were looking at other factors to explain the onset of insanity related to childbirth; stress and environmental factors linked to poverty, family circumstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…In fact, the physicians often attributed the women's mental ailments to contextual factors, such as juvenile maltreatment or abuse (3), alcohol (4), sorrow (2), want (3), chronic disease (2), and sexual excess (1); in five cases it was explicitly noted that the cause was unknown (N ¼ 21). This is in line with Marland (2003), who also reported that doctors in practice, more than stressing purely biological explanations, linked puerperal insanity in women to environmental factors such as poverty, family circumstances, poor nutrition, and so on. Our findings, however, differ from those reported by Koenraadt and Pouw (1987), who-although for a different group, namely women who had been sent directly to Medemblik by a judge, and having access to reports by psychiatrists for the legal process-found relatively more reference to insanity elicited by menstruation and childbirth.…”
Section: Lifestyle and Life Events As Causes For Mental Illnesssupporting
confidence: 78%
“…In fact, the physicians often attributed the women's mental ailments to contextual factors, such as juvenile maltreatment or abuse (3), alcohol (4), sorrow (2), want (3), chronic disease (2), and sexual excess (1); in five cases it was explicitly noted that the cause was unknown (N ¼ 21). This is in line with Marland (2003), who also reported that doctors in practice, more than stressing purely biological explanations, linked puerperal insanity in women to environmental factors such as poverty, family circumstances, poor nutrition, and so on. Our findings, however, differ from those reported by Koenraadt and Pouw (1987), who-although for a different group, namely women who had been sent directly to Medemblik by a judge, and having access to reports by psychiatrists for the legal process-found relatively more reference to insanity elicited by menstruation and childbirth.…”
Section: Lifestyle and Life Events As Causes For Mental Illnesssupporting
confidence: 78%
“…Once committed to an asylum not all patients remained there for life, and families played an important part in the discharge process. Relatives might seek the release of a patient (Coleborne ), especially where mothers were needed at home to care for young children (Marland ). In Victoria, patients whose behaviour had stabilized could be discharged ‘on trial’ (‘O.T.’) to the care of relatives or another responsible person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dessa forma, durante toda a vida, a mulher seria um ser propício a perturbações mentais, e a menstruação estava em destaque nas discussões a respeito desse problema. Marland 10 Rohden 9 observa que a falta de razão de M. A. de F. do B. era evidenciada pela recusa em obedecer ao marido e por expressar desejos eróticos, e que isso só poderia ter ocorrido (conforme acreditavam alguns médicos do período) em virtude das intervenções externas, no caso, a supressão brusca das regras provocada pelo procedimento médico. A autora também salienta que, quando uma mulher realizava um comportamento antisocial, ela não era acusada e, sim, definida como uma vítima ou uma doente, o que retirava dela o poder de demonstrar suas insatisfações em relação à situação que vivia.…”
Section: O Hospício São Pedrounclassified